Agricultura e Futebol: Resistências e ajustamentos no uso do território na Aldeia de Renque Purga, Ilha de Santiago, Cabo Verde - Delgado Silves Ferreira, Vladmir Antero (ILUMINURAS, 2016)
Em Renque Purga na época das chuvas se pratica agricultura e na época seca se retoma à prática de atividades desportivas. Este quadro paisagístico suscita atenção pela sua singularidade e, sobretudo por evidenciar num micro-espaço uma diversidade de questões. Duas atividades humanas se praticam num mesmo espaço, que se transforma num campo de interação entre lógicas de ocupação do território, consideradas antagónicas, que se harmonizam e se coabitam permitindo assim que sejam abordados pelos mesmos parâmetros. Através de uma “etnografia fotografada” lanço um olhar sobre este locus de relação natureza e sociedade tendo como categoria de análise a paisagem e as estratégias de ocupação do território. Palavras-chave: Agricultura. Futebol. Etnografia. Agriculture and soccer: Resistance and adjustments in the use of territory in the Renque Purga Village, Santiago Island, Cape Verde. Abstract In Renque Purga in the rainy season is practiced agriculture and in the dry season is taken to the practice of sports activities. This landscaped framework raises attention for its uniqueness and it shows in a micro-space a variety of issues. Two human activities are practiced in the same space, which becomes a field of interaction between logics of occupation of the territory considered antagonistics, that harmonize and cohabit allowing them to be covered by the same parameters. Through a "photographed ethnography" I will observe this space of relationship between nature and society as an analytical category landscape and occupation strategies of the territory. Keywords: Agriculture. Soccer. Ethnography.